2018
DOI: 10.1002/jcp.27975
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures for HOXA4, HOXA9, and HOXD10 reveal alterations in transcriptional regulatory networks in colon cancer

Abstract: We previously reported that HOXA4, HOXA9, and HOXD10 are selectively expressed in colonic stem cells (SCs) and their overexpression contributes to colorectal cancer (CRC). Our goals here were to determine how these HOX genes are transcriptionally regulated and whether transcriptional dysregulation of HOX genes occurs in CRC. Accordingly, we used correlation analysis to identify genes that are expression‐correlated or anticorrelated with HOXA4, HOXA9, and HOXD10. We then used Gene Ontology (GO) analysis to func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Moreover, it was found that HOXA9 acted as an oncogene in OS development. These findings are consistent with previous research that HOXA9 level is increased markedly in ovarian cancer patients (41) and it was upregulated in colon cancer (42). The higher expression of HOXA9 was associated with OS tumor size, TNM stage and clinical stage.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it was found that HOXA9 acted as an oncogene in OS development. These findings are consistent with previous research that HOXA9 level is increased markedly in ovarian cancer patients (41) and it was upregulated in colon cancer (42). The higher expression of HOXA9 was associated with OS tumor size, TNM stage and clinical stage.…”
Section: Discussionsupporting
confidence: 93%
“…Same as the homeotic genes, retinoids could control the expression of Hox genes. Langston et al [89] identified RARE as part of the regulatory regions of Hox genes and demonstrated the possibility of influencing their transcription by RA. There is reciprocal feedback between HOXA5 and Wnt signalling.…”
Section: Interaction Of Aldh To Main Oncogenic Pathwaysmentioning
confidence: 99%
“…Further studies have shown the role of HOX genes in CSC transformation. For instance, HOXA4 and HOXA9 are enriched during the transformation of colon CSC, and their expression contributes to sustained CSC self-renewal [81]. Upregulation of HOXA9 has also been shown to sustain the self-renewal of HSC in acute myeloid leukemia (AML) and the NUP98-HOXA9 fusion protein induces long-term proliferation and impaired differentiation of leukemic CSC [82,83].…”
Section: Hox Genes In Cancer Stem Cellsmentioning
confidence: 99%